NAVIGATING THE MERDEKA CURRICULUM: INDONESIAN ELEMENTARY TEACHERS’ READINESS AND CHALLENGES IN TEACHING COMPULSORY ENGLISH - Flora; Rafista Deviyanti; Dian Shafwati (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
Indonesia will make English a compulsory subject in elementary schools from 2027, but many primary schools have had little provision for English before now. This study asks how ready elementary English teachers feel for the change and what problems they expect. As the qualitative strand of a larger mixed-methods project, it used semi-structured interviews of five teachers chosen from public and private schools in Lampung Province, analysed through thematic analysis. Four themes emerged: gaps in school resources, differences in teacher readiness and confidence, unequal access to professional development, and shared worries about assessment, parental support, and class size. Four English-trained teachers said they felt ready, most confidently in the private schools; the one teacher without English training did not, and hoped a qualified colleague could join her school. The findings indicate that, without targeted support for resources, training, and teacher qualification, compulsory English may widen the gap between schools rather than close it.